Cleanliness evolution of interstitial free(IF) steel slabs in the thickness direction - WANG Min; BAO Yan-ping; YANG Quan; ZHAO Li-hua; LIN Lu (工程科学学报, 2015)
The cleanness evolution and inclusion distribution of IF slabs in the thickness direction were studied by original morphology analysis, scanning electron microscopy and energy spectroscopy analysis, and total oxygen (T. O) and nitrogen analysis. The average values of mass fraction of total oxygen and N in the slabs in the thickness direction are within 17 × 10-6. The mass fractions of T. O and N in the area within 1/16 thickness from the slab surface are 5% to 10% higher than the average values, in the area between 1/4 thickness from the inner are and 1/4 thickness from the outer arc are 5% to 10% lower than the average values and in other area are close to the average levels. The average size of inclusions is 5.7 txm based on a total of 963 statistical inclusions. Inclusions with the particle size smaller than 5μm account for 60% and with the particle size smaller than 10 txm account for 90%. Al2O3 mainly exits within 5 mm from the slab surface with the size of 2 to 10μm; TiN-Al2O3 and TiN exist in the area from 5 to 80 mm in the thickness direction, and their particle size grows up as the thickness increasing; TiN-TiS and TiS inclusions mainly exist in the area from 80 to 130 mm in the thickness direction with the size of 1 to 5μm. Inclusions from the slab surface to center are mainly Al2O3, Al2O3-TiN, TiN, TiN-TiS, TiS, and MnS in order.